2016
DOI: 10.1016/j.cct.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm experience and Africana culture trial (REACT!): A culturally salient intervention to promote neurocognitive health, mood, and well-being in older African Americans

Abstract: The Rhythm Experience and Africana Culture Trial (REACT!) is a multi-site randomized controlled intervention study designed to examine the efficacy of using African Dance as a form of moderate-intensity physical activity to improve cognitive function in older African Americans. African Americans are almost two times more likely than Caucasians to experience cognitive impairment in late adulthood. This increased risk may be attributed to lower level and quality of education, lower socioeconomic status, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In addition, Stewart et al, [ 65 ] highlighted the need for community physical-activity-promotion programs to be integrated into settings that have the infrastructure, culturally competent staff, access to exercise specialists, and experience in providing outreach and delivering the program to diverse populations. Culturally appropriate interventions have shown mixed results as to their advantage compared to standard interventions; however, most studies are limited due to small target populations, short follow-up, and methodological problems [ 66 ].Yet, they signal the importance of expanding frameworks for practice to be consistent with the reality of diverse community contexts and individuals engaging in pluralistic options and hybrid approaches of PA [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Stewart et al, [ 65 ] highlighted the need for community physical-activity-promotion programs to be integrated into settings that have the infrastructure, culturally competent staff, access to exercise specialists, and experience in providing outreach and delivering the program to diverse populations. Culturally appropriate interventions have shown mixed results as to their advantage compared to standard interventions; however, most studies are limited due to small target populations, short follow-up, and methodological problems [ 66 ].Yet, they signal the importance of expanding frameworks for practice to be consistent with the reality of diverse community contexts and individuals engaging in pluralistic options and hybrid approaches of PA [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a small to moderate sized effect (partial Eta Squared = .31). Pairwise t- tests revealed that this interaction was driven by a significant decrease in weight for the Dance group, t ( 12 ) = 2.38, p =.03, and a marginal increase in weight for the Culture Education group, t ( 10 ) = −2.22, p = .05. The mean weight for each group, at each time point are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 95%
“…After completion of the baseline sessions, participants were randomly assigned to either the African Dance (experimental) or Culture Education (control) group. All classes took place at a local community center located proximally to several predominately African American neighborhoods in Pittsburgh, PA. As with the baseline sessions, the specifics of the Dance and Education intervention groups have been described previously ( 12 ). However, the general structure of each group’s activities are summarized briefly below.…”
Section: Methodsmentioning
confidence: 99%
“…People may be more motivated to participate in a dance that includes familiar steps and music ( Adam et al, 2016 ; Lukach et al, 2016 ; Shanahan et al, 2015 ). Familiar repetitive movement and music can also cue people with CI to be physically active ( Earhart, 2009 ; Lapum & Bar, 2016 ).…”
mentioning
confidence: 99%
“…Familiar repetitive movement and music can also cue people with CI to be physically active ( Earhart, 2009 ; Lapum & Bar, 2016 ). The effects of interventions that use familiar music and steps, matched to participants’ social, historical, or cultural backgrounds and modified to meet their abilities, have been studied and include Salsa dance ( Abreu & Hartley, 2013 ), African dance ( Lukach et al, 2016 ), Malaysian poco-poco dance ( Adam et al, 2016 ), Irish set dance ( Shanahan et al, 2015 ), the Tango ( Hackney et al, 2015 ), and dance-based movement to traditional Korean music ( Kim et al, 2003 ).…”
mentioning
confidence: 99%